Male accessory breast carcinoma: a rare case report and literature review - Luo, Cheng; Wu, Songli; Zeng, Ying; Zhao, Song (Frontiers in Oncology, 2025)
BackgroundAccessory breast carcinoma, arising from embryologically persistent mammary tissue, is exceptionally rare in males, accounting for 2.4%-5.3% of all accessory breast malignancies. Due to limited clinical data, standardized diagnostic and therapeutic protocols remain undefined.Case presentationA 72-year-old male presented with a 3-year history of a painless, mobile right axillary mass. Ultrasonography revealed a solid hypoechoic nodule with moderate vascularity. Histopathological examination confirmed invasive ductal carcinoma (grade II) with infiltrative growth, ER/PR/AR positivity (90%), and TRPS1 expression, confirming mammary origin. Adjuvant therapies were declined by the patient.DiscussionDifferential diagnoses for axillary masses include fibroadenoma, lymphadenopathy, and cutaneous adnexal tumors. Immunohistochemistry (TRPS1, GATA-3) and histomorphology (absence of apocrine differentiation) are pivotal for distinguishing accessory breast carcinoma from mimics. Current management aligns with male breast cancer guidelines, emphasizing surgical resection, lymph node dissection, and adjuvant therapies tailored to molecular profiles. Over 90% of male breast cancers are hormone receptor-positive, warranting endocrine therapy.ConclusionMale accessory breast carcinoma poses significant diagnostic challenges due to its rarity and nonspecific presentation. Clinicians should consider this entity in differential diagnoses of axillary or inguinal masses, irrespective of patient sex. Core needle biopsy and advanced imaging aid preoperative evaluation. Multimodal treatment, including surgery and risk-stratified adjuvant therapies, is critical for optimizing outcomes. This case underscores the need for heightened clinical suspicion and evidence-based guidelines to address this understudied malignancy.